Philosophie de gestion et rôle d’un dirigeant d’entreprise - Noiseaux, Paul (Assurances, 1984)
Mr. Paul Noiseux looks at the qualities required by a manager. He considers in particular a firm of chartered accountants. The qualities he describes are, in general, needed by any commercial enterprise hoping to improve its situation and avoid stagnation or decline. For this, managers need to be intelligent and dynamic, and develop in particular efficiency, aggressivity and a high quality of service. The author is well placed to discuss this subject, in view of the large volume of business handled by his firm, in Canada and abroad.